2018
DOI: 10.1155/2018/2068435
|View full text |Cite
|
Sign up to set email alerts
|

OmpA-Like Proteins of Porphyromonas gingivalis Mediate Resistance to the Antimicrobial Peptide LL-37

Abstract: Subgingival bacteria are continually exposed to gingival crevicular fluids that are derived from serum, which contain various bactericidal agents. The periodontopathic bacterium Porphyromonas gingivalis has been demonstrated to possess a variety of abilities to resist bactericidal agents, due to which it is able to propagate in the subgingival environment. We previously demonstrated that the major surface glycoproteins of P. gingivalis—Pgm6 and Pgm7, also called outer membrane protein A-like proteins (OmpALPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…When LL-37 binds to AbOmpA, it can inhibit motility and adhesion of A. baumannii; although A. baumannii is considered a non-motile bacterium, it has the capability to migrate under certain conditions [63]. In Escherichia coli and other enterobacteria, OmpA acts as an adhesion and invasion [63], and outer membrane protein A-like proteins (OmpALPs) in Porphyromonas gingivalis serves as a protection against LL-37 accumulation on the surface of the cell [64]. Mutations in both the ompA [63] and OmpALP [64] results in a greater sensitivity to LL-37.…”
Section: Outer Membrane Proteins and Vesiclesmentioning
confidence: 99%
See 3 more Smart Citations
“…When LL-37 binds to AbOmpA, it can inhibit motility and adhesion of A. baumannii; although A. baumannii is considered a non-motile bacterium, it has the capability to migrate under certain conditions [63]. In Escherichia coli and other enterobacteria, OmpA acts as an adhesion and invasion [63], and outer membrane protein A-like proteins (OmpALPs) in Porphyromonas gingivalis serves as a protection against LL-37 accumulation on the surface of the cell [64]. Mutations in both the ompA [63] and OmpALP [64] results in a greater sensitivity to LL-37.…”
Section: Outer Membrane Proteins and Vesiclesmentioning
confidence: 99%
“…In Escherichia coli and other enterobacteria, OmpA acts as an adhesion and invasion [63], and outer membrane protein A-like proteins (OmpALPs) in Porphyromonas gingivalis serves as a protection against LL-37 accumulation on the surface of the cell [64]. Mutations in both the ompA [63] and OmpALP [64] results in a greater sensitivity to LL-37. It is suggested that in the absence of ompA, LL-37 will bind to other OMPs that exhibit higher permeability and pore-forming ability, which increases the level of cell death [63].…”
Section: Outer Membrane Proteins and Vesiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since LL-37 exerts bactericidal and antiinflammatory activities by binding to LPS, the degradation of this peptide also abolishes its anti-inflammatory effect and promotes the release of TNF-a, contributing to the development of late-onset periodontitis (Koneru et al, 2017). In addition to T. forsythia, P. gingivalis has evolved a mechanism to abolish the bactericidal activity of LL-37 by its outer membrane protein A-like proteins, preventing the accumulation of LL-37 on the bacterial surface (Horie et al, 2018). These bacteria can also inhibit the serine protease activity.…”
Section: Resistance To Granule-mediated Killingmentioning
confidence: 99%